2020
DOI: 10.1093/ndt/gfaa134
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for venous thromboembolism in patients with nephrotic syndrome: a retrospective cohort study

Abstract: Background Nephrotic syndrome is associated with an increased risk of venous thromboembolism (VTE). However, the risk factors of VTE in nephrotic syndrome, other than hypoalbuminemia and severe proteinuria, are not well established. Therefore we aimed to investigate the risk factors of VTE in patients with nephrotic syndrome. Methods This retrospective cohort study used data from a Japanese nationwide claims database. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
4
25
0
1
Order By: Relevance
“…The histopathological findings in both our cohorts were similar to those reported in patients with NS in the Netherlands (8), and Japan (10,22), with the most common being: minimal change disease, membranous nephropathy, mesangioproliferative glomerulopathy, and focal segmental glomerulosclerosis, possibly reflecting that patients with biopsy in both cohorts were selected for nephrology review. Similarly to previous studies, diabetic nephropathy was rarely reported in pathology records despite high prevalence of diabetes in our cohorts, likely due to a reluctance to perform kidney biopsies in patients with diabetes (8)(9)(10).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The histopathological findings in both our cohorts were similar to those reported in patients with NS in the Netherlands (8), and Japan (10,22), with the most common being: minimal change disease, membranous nephropathy, mesangioproliferative glomerulopathy, and focal segmental glomerulosclerosis, possibly reflecting that patients with biopsy in both cohorts were selected for nephrology review. Similarly to previous studies, diabetic nephropathy was rarely reported in pathology records despite high prevalence of diabetes in our cohorts, likely due to a reluctance to perform kidney biopsies in patients with diabetes (8)(9)(10).…”
Section: Discussionsupporting
confidence: 83%
“…Nephrotic syndrome (NS) is a clinical diagnosis defined by biochemical criteria of nephrotic proteinuria (>3.5 gram per day), hypoalbuminemia, and the presence of edema (1,2). Data on the occurrence and prognosis of NS in adults are limited (3), and previous epidemiological studies of NS have focused on patients with NS recorded in hospital or pathology databases (4)(5)(6)(7)(8)(9)(10). However, NS can present insidiously, and patients may seek the help of a range of specialists before receiving specialist care from hospital doctors.…”
Section: Introductionmentioning
confidence: 99%
“…The following seven types of diagnostic information are recorded only in the DPC claims: “main condition,” “other condition,” “trigger‐for‐hospitalization condition,” “most resource‐consuming condition,” “second most resource‐consuming condition,” “comorbidities present on admission,” and “conditions occurring after admission.” Patients in the database can be tracked as long as they are treated in the same hospital. The database has been used to evaluate cardiovascular issues 20,21 . For the present study, the study protocol was approved by the ethics committee of Kyoto University Graduate School and Faculty of Medicine (approval number: R2610), but informed consent was not required because the data were anonymous.…”
Section: Methodsmentioning
confidence: 99%
“…Because no validation studies on the definition of VTE recurrence have been conducted in Japan, this outcome was determined in consultation with an expert cardiologist, using a combination of the following two components: (1) inpatient diagnosis recorded in the DPC claim of VTE as "main condition," "trigger-for-hospitalization condition," "most resource-consuming condition," or "conditions occurring after admission"; and (2) imaging procedure codes during hospitalization. 21,22 We excluded recurrent VTE during hospitalization of the index VTE to ensure one VTE episode per hospitalization. As in the previous study, 14 we did not include VTE diagnoses in the outpatient setting because they might imply not a recurrence but a follow-up visit.…”
Section: Study Outcomesmentioning
confidence: 99%
“…While most studies indicated that the higher proteinuria and lower serum albumin could predict VTE [33, 34], female gender, body mass index over 30, acute kidney injury, nephritis associated with lupus, sepsis, and the use of intravenous corticosteroid may contribute to the risk of developing VTE according to a recent study [35]. In addition, histopathological subtype was an independent risk factor for occurring VTE, even adjusted for other factors (history of cancers, proteinuria, patient’s gender, and serum albumin), with the highest risk in MN groups [36].…”
Section: Ns and Vtementioning
confidence: 99%